Biological management of coffee wilt disease (Fusarium xylarioides) using antagonistic Trichoderma isolates - Mulatu, Afrasa; Megersa, Negussie; Teferi, Demelash; Alemu, Tesfaye; Vetukuri, Ramesh Raju (Frontiers in Plant Science, 2023)
Coffee wilt disease (CWD) is a serious threat to the food security of small-scale farmers in Ethiopia, causing significant reductions in coffee yield. Currently, there are no effective control measures available against the causative agent of CWD, Fusarium xylarioides. The main objective of this study was therefore to develop, formulate, and evaluate a range of biofungicides against F. xylarioides, derived from Trichoderma species and tested under in vitro, greenhouse, and field conditions. In total, 175 Trichoderma isolates were screened as microbial biocontrol agents against F. xylarioides. The efficacy of two biofungicide formulations, wettable powder and water dispensable granules, were tested on the susceptible Geisha coffee variety in three different agro-ecological zones in southwestern Ethiopia over three years. The greenhouse experiments were set up using a complete block design, while in the field a randomized complete block design was used, with twice yearly applications of biofungicide. The test pathogen spore suspension was applied to the coffee seedlings by soil drenching, and the subsequent incidence and severity of CWD evaluated annually. The mycelial growth inhibition profiles of the Trichoderma isolates against F. xylarioides ranged from 44.5% to 84.8%. In vitro experiments revealed that T. asperelloides AU71, T. asperellum AU131 and T. longibrachiatum AU158 reduced the mycelial growth of F. xylarioides by over 80%. The greenhouse study indicated that wettable powder (WP) of T. asperellum AU131 had the highest biocontrol efficacy (84.3%), followed by T. longibrachiatum AU158 (77.9%) and T. asperelloides AU71 (71.2%); they also had a significant positive impact on plant growth. The pathogen-treated control plants had a disease severity index of 100% across all the field experiments, and of 76.7% in the greenhouse experiments. In comparison to untreated controls, the annual and cumulative disease incidence over the three years of the study period varied from 46.2 to 90%, 51.6 to 84.5%, and 58.2 to 91%, at the Teppi, Gera and Jimma field experimental locations. Overall, the greenhouse and field experiments and in vitro assays support the biocontrol potential of Trichoderma isolates, and T. asperellum AU131 and T. longibrachiatum AU158 in particular are recommended for the management of CWD under field conditions.